Public health diplomacy: summary of the methods and outcome of the 1st University of Memphis School of Public Health Diplomacy Summit - Joshi, Ashish; Magana, Laura; Tsai, Kun-Hsien; Maddah, Diana; Mitchell, Kerry; Ruggiero, Diana; Hawkins, W. Bradley; Dharamsi, Shafik; Makhoul, Jihad; Reis, Rodrigo; Kim, So Yoon; Low, Wah Yun; et al. (Frontiers in Public Health, 2025)
Public health diplomacy addresses global challenges impacting societies, economies, the environment, and health by integrating foreign policy and development. The University of Memphis School of Public Health hosted a multistakeholder summit to identify strategies and competencies essential for effective public health diplomacy. A 3-day summit included 29 participants from 15 countries, representing the WHO, the World Federation of United Nations, and seven regional public health associations. An iterative human-centered design (HCD) approach and concept mapping were employed to facilitate discussions and generate actionable recommendations. Developed a working definition of Public Health Diplomacy emphasizing cross-disciplinary collaborations, communication, negotiation, and consensus building. Produced a 9-point action plan to establish a global framework, launch capacity-building initiatives, and institutionalize public health diplomacy as a public health discipline.